Effect of water and mechanical retting process on mechanical and physical properties of kenaf bast fiber reinforced unsaturated polyester composites. (1st February 2021) - Rozyanty, A.R.; Zhafer, S.F.; Shayfull, Z.; Nainggolan, I.; Musa, L.; Zheing, L.T.
Abstract: The properties of polymer composite filled or reinforced with kenaf fiber have been extensively studied in recent decades as an alternative for replacing synthetic fiber in composite structures. Although many studies have been conducted on natural fiber filled or reinforced composite, lack of researches have been done on the processing factors that contributed to the overall fiber strength. Thus, this study aims to determine the efficiency of retting process which significantly influences the characteristics and performance of the final composite products. In this study, the kenaf bast fibers composites were prepared using hand lay-up method at different fiber loadings (weight%) of 10, 15, 20, 25, 30 and 35 through two retting methods namely water and mechanical retting process. Unsaturated polyester (UPE) resin and methyl ethyl ketone peroxide (MEKP) were used as binder and catalyst, respectively. This current research aims to examine the effects of different retting processes and fiber loadings on tensile strength, water absorption and morphology which consists of tensile fracture and fiber surface, using Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The tensile strength of water retted kenaf bast fibers reinforced UPE composites exhibited higher value than mechanical retted kenaf bast fibers reinforced UPE composites. In terms of water absorption, it was found that mechanical retted kenaf bast fiber reinforced UPE composites absorb more moisture than water retted kenaf bast fibers reinforced UPE composites. From the results, it can be concluded that the water retting process yielded higher mechanical and water absorption properties compared to mechanical retting process at all different fiber loadings (weight%). This current study contributes to the current field of knowledge by providing a clear reference for future development of high-performance polymer composites based on kenaf bast fibers as reinforcements, specifically in structural applications such as floor decking, door and window frames.